KAFURA DALAM AL-QU’RAN DAN HADIS: TELAAH HISTORIS - LINGUISTIK ATAS JEJAK KAPUR BARUS - Siti Kholidah Marbun; Ira Novita Sari; Nanda Sekti Prayetno (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
This study examines the term kafura as it appears in Surah al-Insan (76:5) of the Quran and in the saying of the Prophet Muhammad saw. from historical and linguistic perspective. The purpose of thus research is ti trace the etymologi and semantic development of the term kafura, its usage in religious texts, and its possible connection to the trading commodity known as canphor (Kapur barus) originating from the Barus region in North Sumatera, Indonesia. The research employs a qualitative methodology with a historical-linguistic approach, drawing on primary sources such as classical Quranic exegesis (tafsir), hadith collection, travelogues, and historical chronicles from the Islamic world, China, and the West. The findings indicate that kafura, as interpreted by Nusantaran scholars, reflects a historical link between the term and natural products from the Malay-Indonesian archipelago, which had long been part of global trade networks both before and after the advent of Islam. From a linguistic perspective, the study suggests that the inclusion of foreign loan words in the Qur’an, kafura among them is a form of ta‘rib (Arabization), possibly mediated through Persian, which supports the notion of early intercultural and commercial interactions in the pre-Islamic era. Historically, camphor from Barus (also known as Fansur), located on the western coast of Sumatra, was a highly valued international commodity known across the ancient world since the early Common Era. In conclusion, this study posits that kafura is a cross-cultural term that underscores the significant role of Barus in the networks of trade and the dissemination of Islam in the Asian region.